2009
DOI: 10.1093/ije/dyp280
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of epidemiologic studies on cigarette smoking and liver cancer

Abstract: The results of our meta-analysis show that tobacco smoking is associated with liver cancer development, which supports the conclusion by the IARC Monograph. This conclusion has an important public health message for areas with high smoking prevalence and high liver cancer incidence such as China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
5
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 80 publications
9
171
5
2
Order By: Relevance
“…Another meta analysis by Lee, et al got an overall RR of 1.51 (95% CI: 1.37-1.67) and 1.12 (95% CI: 0.78-1.60), respectively. And the increased risk among current smokers was consistent when stratified by region, design, sample size and publication period and a positive dose-response relationship was also observed (Lee et al, 2009).…”
Section: Tobaccosupporting
confidence: 54%
“…Another meta analysis by Lee, et al got an overall RR of 1.51 (95% CI: 1.37-1.67) and 1.12 (95% CI: 0.78-1.60), respectively. And the increased risk among current smokers was consistent when stratified by region, design, sample size and publication period and a positive dose-response relationship was also observed (Lee et al, 2009).…”
Section: Tobaccosupporting
confidence: 54%
“…Alcohol and other risk factors also make a contribution. A meta-analysis that carefully considered the confounding influence of alcohol, HBV, and HCV found RRs of 1.4-1.5 for liver cancer for current versus never smokers [30].…”
Section: Brief Overview Of Smoking-cancer Associationsmentioning
confidence: 99%
“…Cigarette smoking, positive HBeAg carrier status and chronic hepatitis all contribute synergistically to the development of liver cirrhosis (Yu et al, 1997). A meta-analysis showed that tobacco was associated with liver cancer development (Lee et al, 2009). There was a dose-response relationship between the consumption of alcohol and the development of HCC, 'heavy drinkers' having an approximately 3-4 fold risk increase, compared with non-drinkers (Zhang et al,1998).…”
Section: Discussionmentioning
confidence: 99%